Synthesis, morphology, characterisation, and ethanol gas sensing of hierarchical flower-like Co-doped WO3 nanoplates by solvothermal route - Lim, Jong-Chan; Jin, Changhyun; Choi, Myung Sik; Kim, Min Young; Kim, Sang-il; Choi, Soon-Mok; Baek, Seung-Hyub; Lee, Kyu Hyoung; Kim, Hyun-Sik (ELSEVIER SCI LTD, 2021)
Three-dimensional flower-like tungsten oxide nanoplates sequentially doped with Co at different concentrations were fabricated using a single solvothermal process. The response of the nanostructure of the n-type tungsten oxide used for sensing ethanol gas, which is a reducing gas, changed sequentially according to the process temperature and doping concentration of Co. This response cannot be attributed to a single reason, but it can be regarded as a result of the combination of several complicated direct and indirect phenomena such as (1) point, line, and cross-section defects on the surface, (2) change in initial resistance corresponding to doping concentration, (3) catalytic effect of dopant, and (4) difference in energy level at heterojunctions. Therefore, unlike in the case of other gas sensing methods that depend on a main cause or mechanism, it might be meaningful in the case of ethanol gas sensing to analyse each cause and predict the results of different combinations.
Keywords: SEMICONDUCTING METAL-OXIDES; ORGANIC-COMPOUNDS VOCS; SCHOTTKY-JUNCTION; SENSORS; GRAPHENE; NANOSTRUCTURES; PLATINUM; FILMS; MOS2; XPS